Sampai Maut Memisahkan kita ? (Tafsir Matius 19:3-12 Diperhadapkan dengan Keberpihakan Gereja Terhadap Istri Korban KDRT) - Pdt Paulina Herlina Norayanti Sirait (Jurnal Teologi Cultivation, 2020)
Till Death do us part?(Interpretation of Matthew 19:3-12 Faced with the Partisanship of the Church Against the Wife of the Victim of domestic violence)ABSTRACT Actually, the happy marriage of the coveted all pairs when beginning a commitment to bind themselves in marriage, accompanied by a promise to be loyal to live together in all situations: hard – fun,  sick – healthy, poor – rich,  until the end of life. But in fact, problems in the marriage are increasingly complex. The problems of the household that is increasingly complicated solved, contribute to the cause of the high divorce rate.HKBP as a protestant church in Southeast Asia uphold the integrity of the marriage of the citizens of his congregation, and impose strict regulations against the case of divorce, founded on the Word of God in the Bible: What God has joined together, let not man put asunder, except for sexual immorality (Matthew 19:6, 9). The problem is, there are certain cases in marriage not because of adultery, but has led to the loss of the existence of the marriage, such as acts of domestic violence that occur repeatedly and chronically, but not applicable as an excuse to allow the occurrence of divorce.This Paper assesses the return of Matthew 19:3-12 for the divorce, which faced up to the alignments of the church against victims of domestic VIOLENCE. With the interpretation of the more comprehensive, the church will bring news of liberation for women oppressed in a marital situation which is difficult.TAGS: Marriage, Divorce, domestic Violence, HKBP